Особливості формування вокально-технічних умінь студентів факультетів миситецтв на засадах герменевтичного підходу - Ван Чжибінь; Wan Zhibin (Видавництво «Код», 2025)
Резюме. У статті розкривається проблема формування вокально-технічних умінь студентів факультетів мистецтв на засадах герменевтичного підходу. Розглянуто витоки герменевтики як теорії розуміння, тлумачення та інтерпретації в історикофілософському аспекті. Виявлено особливості принципу «герменевтичного кола» в філософських концепціях В. Дільтея та Ф. Шляйєрмахера, розкрито специфіку набуття герменевтичного досвіду згідно теорії Г.-Ґ. Ґадамера. Визначено значущість ідей герменевтичного вчення для педагогічної науки, оскільки проблема знання й проблема розуміння цього знання включені в загальний процес освоєння людиною навколишньої дійсності і поза цією діяльністю втрачають своє значення й зміст. За цих умов актуалізується значення герменевтичного підходу, за допомогою якого дослідник проникає в суть певного педагогічного явища і в процесі наукового аналізу пропонує своє бачення інтерпретації цих явищ.

Abstract. The article reveals the problem of the formation of vocal-technical skills of students of art faculties on the basis of the hermeneutic approach. The origins of hermeneutics as a theory of understanding, interpretation and interpretation in the historical and philosophical aspect are considered. The features of the principle of the "hermeneutic circle in the philosophical concepts of W. Dilthey and F. Schleiermacher are revealed, the specifics of acquiring hermeneutic experience according to the theory of H.-G. Gadamer are revealed. The significance of the ideas of hermeneutic teaching for pedagogical science is determined, since the problem of knowledge and the problem of understanding this knowledge are included in the general process of a person’s mastery of the surrounding reality and outside of this activity lose their meaning and content. Under these conditions, the significance of the hermeneutic approach is actualized, with the help of which the researcher penetrates the essence of a certain pedagogical phenomenon and in the process of scientific analysis offers his vision of the interpretation of these phenomena. It is found out that hermeneutics as the art of interpretation and understanding acts as a worldview and methodological basis for the knowledge of artistic phenomena. From these positions it is substantiated that the hermeneutic approach acquires special importance in the content of musical, in particular, vocal training of students of artistic specialties, the effectiveness of which largely depends on the worldview paradigm within which the professional training of the future singer takes place. The introduction of the ideas of hermeneutic teaching into the content of vocal training contributes to the establishment of the priority of the spiritual formation of the student’s personality over the formal indicators of his success, especially in terms of the formation of vocal and technical skills. It is proven that the hermeneutic approach as a modern methodological tool makes it possible to study the problem of the formation of vocal and technical skills as a dialogical process, in which the teacher acts not only as an instructor, but also as a co-interpreter, who, together with the student, immerses himself in the semantic field of both methodological issues and the artistic performance of the work.
Features of the formation of vocal-technical skills of students of mystics faculties on the basis of the hermeneutic approach
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: герменевтика; інтерпретація; розуміння; герменевтичний підхід; студенти факультетів мистецтв; вокальне навчання; вокально-технічні вміння; вища мистецька освіта